Implementasi Pembelajaran Pendidikan Agama Islam Berbasis Wasathiyah Dalam Pembentukan Karakter Siswa Mtsn 4 Aceh Besar - Safrizal (PT. Hasba Edukasi Mandiri, 2025)
Islam teaches wasathiyah or moderate attitudes in religious matters, namely the teachings to be fair, balanced, beneficial, and proportional in every aspect of life. This concept is directly derived from the Holy Quranic Verses which are believed to be able to make Muslims superior and relevant in facing the era of globalization and the latest technological advances. This study aims to determine the application of wasathiyah-based Islamic Religious Education (PAI) learning and the implications of this learning on the attitudes and characters of MTsN 4 Aceh Besar students. This study uses a qualitative method with a field research approach, namely research whose objects are regarding the symptoms or events that occur in the community groups at MTsN 4 Aceh Besar. The results of the study indicate that the application of wasathiyah-based PAI learning at MTsN 4 Aceh Besar is seen through good student behavior and reflects the values of religious moderation. The implications are seen in the improvement of students' religious and social attitudes, such as respecting teachers, diligently praying, caring for society, obeying rules, and being tolerant.